A retrospective cohort study of early mortality among patients with HIV/TB co‐infection in Shanghai municipality. Issue 11 (25th December 2020) - Qi, TK; Chen, J; Zhang, RF; Liu, L; Shen, YZ; Wang, ZY; Sun, JJ; Song, W; Tang, Y; Wang, JR; Ling, YX; Xu, SB; et al.
Abstract : Objectives: Tuberculosis (TB) is the most common and fatal opportunistic co‐infection among HIV‐infected individuals. While TB‐associated mortality predominantly occurs in the first 90 days after admission, such a correlation remains unclear in HIV/TB co‐infected patients. Thus, we aimed to investigate the 90‐day mortality and associated risk factors among HIV/TB co‐infected patients in China. Methods: Adult patients with HIV and a newly confirmed TB diagnosis admitted to the Shanghai Public Health Clinical Center between September 2009 and August 2017 were enrolled. Clinical and laboratory characteristics, key treatments and outcomes were collected retrospectively. The associations between different factors and early mortality were analysed. Results: Of the 485 laboratory‐confirmed HIV/TB patients [median (range) age = 39 (19–79) years], 413 (85.15%) were male. Diagnosis was confirmed by culture, pathology and acid‐fast bacilli smear alone in 362 (74.6%), 6 (1.2%) and 117 (24.1%) patients, respectively. Multiple drug‐/rifampin‐resistant TB was detected in 21 (5.8%) of the 367 patients with a positive culture. Rifampin or rifabutin was administered to 402 (82.9%) patients. Additionally, 66 (13.6%) and 86 (17.7%) died within 90 days and 1 year of admission, respectively. Of the 64 TB‐related deaths, 59 (92.2%) occurred within 90 days of admission. In Cox regression, central nervous system (CNS) TB [odds ratio (OR) = 2.49, 95% confidence interval (CI): 1.46–4.23, P  < 0.001], no antiretroviral therapy (ART) within 3 months after admission (OR = 11, 95% CI: 6.4–18.9, P  < 0.001), and plasma albumin level < 25 g/L (OR = 1.91, 95% CI: 1.07–3.40, P  = 0.021) were associated with early death. Conclusions: Tuberculosis co‐infection was prevalent and fatal in HIV‐infected patients, with most deaths occurring within 90 days of admission. Early mortality was associated with CNS‐TB, no ART, and serum albumin level < 25 g/L.